Spiral spin liquid noise - Takahashi, Hiroto; Hsu, Chun-Chih; Jerzembeck, Fabian; Murphy, Jack; Ward, Jonathan; Enright, Jack D; Knapp, Jan; Puphal, Pascal; Isobe, Masahiko; Matsumoto, Yosuke; Takagi, Hidenori; Davis, J C Séamus; et al. (Proceedings of the National Academy of Sciences - PNAS, 2025)
An emerging concept for identification of different types of spin liquids [C. Broholm , , eaay0668 (2020)] is through the use of spontaneous spin noise [S. Chatterjee, J. F. Rodriguez-Nieva, E. Demler, , 104425 (2019)]. Here, we develop spin noise spectroscopy for spin liquid studies by considering Ca Cr O , a material hypothesized to be either a quantum or a spiral spin liquid (SSL). By enhancing techniques introduced for magnetic monopole noise studies [R. Dusad , , 234-239 (2019)], we measure the time and temperature dependence of spontaneous flux [Formula: see text] and thus magnetization [Formula: see text] of Ca Cr O samples. The resulting power spectral density of magnetization noise [Formula: see text] reveals intense spin fluctuations with [Formula: see text] and [Formula: see text]. Both the variance [Formula: see text] and the correlation function [Formula: see text] of this spin noise undergo crossovers at a temperature [Formula: see text]. While predictions for quantum spin liquids are inconsistent with this phenomenology, those from Monte-Carlo simulations of a two-dimensional (2D) SSL state in Ca Cr O yield overall quantitative correspondence with the measured frequency and temperature dependences of [Formula: see text], and [Formula: see text], thus indicating that Ca Cr O is an SSL.